On the origin of perpendicular magnetic anisotropy in strained Fe–Co(–X) films. (4th January 2017) - Reichel, L; Edström, A; Pohl, D; Rusz, J; Eriksson, O; Schultz, L; Fähler, S
Abstract: Very high magnetic anisotropies have been theoretically predicted for strained Fe–Co(–X) and indeed several experiments on epitaxial thin films seemed to confirm strain induced anisotropy enhancement. This study presents a critical analysis of the different contributions to perpendicular anisotropy: volume, interface and surface anisotropies. Tracing these contributions, thickness series of single layer films as well as multilayers with Au–Cu buffers/interlayers of different lattice parameters have been prepared. The analysis of their magnetic anisotropy reveals a negligible influence of the lattice parameter of the buffer. Electronic effects, originating from both, the Au–Cu interface and the film surface, outrange the elastic effects. Surface anisotropy, however, exceeds the interface anisotropy by more than a factor of three. A comparison with results from density functional theory suggests, that the experimentally observed strong perpendicular surface anisotropy originates from a deviation from an ideal oxide-free surface. Accordingly, tailored Fe–Co–X/oxide interfaces may open a route towards high anisotropy in rare-earth free materials.